Fabrication of nano‐encapsulated angelica (Heracleum persicum) essential oil for enriching dairy dessert: Physicochemical, rheological and sensorial properties - Narin Mhemmedamin Nanakali (IET Nanobiotechnology)
Abstract In this study, the nanoemulsions containing angelica essential oil (AEO) was used as a novel nano‐carrier for enrichment of dairy dessert. Firstly, oil‐in‐water nanoemulsions were prepared by different levels of GE (1%, 5%, 10%, and 15%) as the dispersed phase, Tween 80 as surfactant with a constant surfactant to essential oil ratio (1:1), and distillated water as a continuous phase. Droplet size, free radical scavenging capacity, antimicrobial activity against gram‐positive (Staphylococcus aureus (25923 ATCC)) and gram‐negative (Escherichia coli H7 O157 (700728 ATCC)) were evaluated for produced nanoemulsions. The mean droplet size of nanoemulsion increased from 75 to 95 nm and antioxidant capacity also enhanced from 15.4% to 30.2% by increasing AEO level from 1% to 15%. Antimicrobial analysis by disk diffusion methods for nanoemulsions containing different levels of AEO cleared that nanoemulsions with high levels of AEO showed the stronger antimicrobial activity against both used bacteria and especially more activity against Staphylococcus aureus. The results of the total count and yeast and mould count show that the nanoemulsions with different levels of AEO have been effective on the number of microorganisms, particularly during storage. The incorporation of pure essential oil and nanoemulsions with different levels of AEO did not affect significantly the pH of different dessert samples however, they affected the dry matter and free radical scavenging capacity. Adding of nanoemulsions with different levels of AEO to the desserts had a considerable effect on the rheological properties including apparent viscosity, Gʹ, G", Tan δ and complex viscosity and all samples showed shear‐thining behaviour. Results from organoleptic characteristics (taste, odour colour, mouthfeel and total acceptance) showed that enriched samples by nanoemulsions, particularly with higher level of AEO had higher sensorial scores. In general, samples containing free AEO (not encapsulated) had the lower scores in all organoleptic characteristics.